Legal Protection Against Notaries In The Process of Authentic Deed Processing - Afdol; Baby Nita Selly Veronika (Faculty of Law, Merdeka University Surabaya, 2021)
The position of a notary is very necessary in the business world, because it is in accordance with its duties which is to record civil actions and set out in an authentic deed. source of data used in this study is secondary data consisting of primary legal materials in the form of basic norms/rules and related laws and regulations. with the law of protection of notaries in particular The type of research in this legal research is normative legal research, which is a process to find legal rules, legal principles, and legal doctrines in order to answer legal issues faced Engineering and data collection in research This is done by means of library research. Data collection tools used are document studies to obtain secondary data, by reading, studying, researching, analyzing secondary data, secondary and tertiary related to this research.